Prevalence and prognostic value of psychological stress events in patients with first myocardial infarction-Long-term follow-up study - Jaensch, Andrea; Schöttker, Ben; Schmucker, Roman; Koenig, Wolfgang; Brenner, Hermann; Rothenbacher, Dietrich (Journal of Clinical Medicine, 2021)
While there is good evidence that symptoms of depression determine prognosis of patients with coronary heart disease (CHD), the role of psychological stress is less clear. We evaluated the prognostic value of stressful events in patients with initial myocardial infarction (MI) with respect to subsequent cardiovascular events. The KAROLA-study included patients with CHD who participated in an in-patient rehabilitation program. A total of 577 patients with initial MI were included and self-reported psychological stressful events before their MI was assessed by a structured questionnaire. Hazard ratios were used to evaluate the long-term association of stressful events with secondary cardiovascular events. Additionally, associations of stressful events with depression, anxiety and other cardiovascular risk factors were investigated. Unusual stress at work (26.5%) and sleep disorder (23.4%) were the most frequently reported stressful events that occurred in the last 4 weeks before MI. However, only death of a family member showed a statistically significant increase in risk for subsequent cardiovascular events (HR: 1.59; 95%-CI: 1.01-2.50) and this result was not corrected for multiple testing. Notably, we found higher symptom scores of anxiety and depression associated with all single stressful event items. In conclusion, we found no clear patterns that psychological stressful events before MI would increase the long-term risk of subsequent adverse CHD events directly. However, we saw increased symptom scores of anxiety and depression in persons with stressful events.
Gesehen am 15.12.2021